(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Despite being an Ecologically Critical Area (ECA) and a key attraction place for its uniqueness and unique bird fauna to the bird watchers and researchers, a method-based, scientific checklist on the avifauna of the Saint Martin’s Island is still lacking. This study was attempted to fill in this gap and produced an annotated bird checklist for the St. Martin’s island. A total of 112 species of birds belonging to 36 families under 15 orders was listed. Of these, 37 (33%) species were passerine and 75 (67%) species were nonpasserine. Eleven (9.82%) species were found to be very common, 12 (10.72%) species common, nine (8.04%) species uncommon and 80 (71.43%) species rare. Asiat. Soc. Bangladesh, Sci. 44(2): 149-158, December 2018